2004
DOI: 10.1021/ja0463482
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile-Functionalized Pyridinium Ionic Liquids:  Synthesis, Characterization, and Their Application in Carbon−Carbon Coupling Reactions

Abstract: A series of relatively low-cost ionic liquids, based on the N-butyronitrile pyridinium cation [C(3)CNpy](+), designed to improve catalyst retention, have been prepared and evaluated in Suzuki and Stille coupling reactions. Depending on the nature of the anion, these salts react with palladium chloride to form [C(3)CNpy](2)[PdCl(4)] when the anion is Cl(-) and complexes of the formula [PdCl(2)(C(3)CNpy)(2)][anion](2) when the anion is PF(6)(-), BF(4)(-), or N(SO(2)CF(3))(2)(-). The solid-state structures of [C(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
260
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(270 citation statements)
references
References 37 publications
(52 reference statements)
9
260
0
1
Order By: Relevance
“…The practical viability of the palladium-poly(ionic liquid) catalyst membranes in the present study has been demonstrated for the Suzuki--Miyaura coupling reaction of iodobenzene. The measured TOF value of 3097 ± 323 h −1 for heated (343 K) batch reaction mode is comparable with previously reported homogeneous ionic liquid catalysts (TOFs of 10 The palladium membrane loadings used for the Suzuki-Miyaura coupling reaction (a reaction solution equivalent of 0.061 ± 0.004 mol % or 11.1 ± 8 ppm on a mass basis) are lower than most previously reported ionic liquid catalysts (homogeneous and heterogeneous) which range between 0.1-18 mol% [5,[7][8][9][10][11][12][14][15][16]22,64]. A palladium leaching value of 83 ppb h −1 cm −3 at 343 K compares favourably with previously reported solid support heterogeneous catalysts (where palladium leaching rates exceed 100 ppb h −1 cm −3 ) [65,66].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The practical viability of the palladium-poly(ionic liquid) catalyst membranes in the present study has been demonstrated for the Suzuki--Miyaura coupling reaction of iodobenzene. The measured TOF value of 3097 ± 323 h −1 for heated (343 K) batch reaction mode is comparable with previously reported homogeneous ionic liquid catalysts (TOFs of 10 The palladium membrane loadings used for the Suzuki-Miyaura coupling reaction (a reaction solution equivalent of 0.061 ± 0.004 mol % or 11.1 ± 8 ppm on a mass basis) are lower than most previously reported ionic liquid catalysts (homogeneous and heterogeneous) which range between 0.1-18 mol% [5,[7][8][9][10][11][12][14][15][16]22,64]. A palladium leaching value of 83 ppb h −1 cm −3 at 343 K compares favourably with previously reported solid support heterogeneous catalysts (where palladium leaching rates exceed 100 ppb h −1 cm −3 ) [65,66].…”
Section: Discussionsupporting
confidence: 81%
“…In the case of the Suzuki-Miyaura carbon-carbon coupling reaction, palladium species immobilised within ionic liquids have been shown to be highly effective catalyst systems [4][5][6][7][8][9][10][11][12][13][14][15][16]. For instance, ionic liquid imidazolium cations can coordinate palladium catalyst centres [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The use of external capping agents, or functionalised ILs such as 2,2 0 -dipyridylamine-functionalised imidazolium salts, 35 polymers 36 or ionic carbon nanotubes 37 have been used for the stabilisation and dispersion of Pd-NPs in ILs. Indeed, nitrile functionalised ILs seem to offer one of the best media for the generation of catalytically active Pd nanoparticles 38 since it binds to the metal surface providing the stabilisation, but allows the coordination of substrates. 22 We report herein our preliminary results for the synthesis of Pd(0)-NPs in ILs and their use as efficient catalysts for the partial hydrogenation of alkynes to alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…The MacMillan case more closely resembles the nickel-catalyzed Suzuki, Stille, and Kumada coupling of aryldiazonium salts, which have been known for some time. 6 There are no examples in the literature of any metal-mediated vinylpyridinium or vinyltrialkylammonium salt carboncarbon bond formation, 7 and furthermore, the corresponding vinyldiazonium salts are unknown. Accordingly, these salts represent a completely new and useful class of palladiumcatalyzed electrophilic coupling partner.…”
mentioning
confidence: 99%